2020
DOI: 10.3389/fneur.2020.588531
|View full text |Cite
|
Sign up to set email alerts
|

Blast in Context: The Neuropsychological and Neurocognitive Effects of Long-Term Occupational Exposure to Repeated Low-Level Explosives on Canadian Armed Forces' Breaching Instructors and Range Staff

Abstract: Currently, there is strong interest within the military to better understand the effects of long-term occupational exposure to repeated low-level blast on health and performance. To gain traction on the chronic sequelae of blast, we focused on breaching—a tactical technique for gaining entry into closed/blocked spaces by placing explosives and maintaining a calculated safe distance from the detonation. Using a cross-sectional design, we compared the neuropsychological and neurocognitive profiles of breaching i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 65 publications
0
13
0
5
Order By: Relevance
“…In earlier research involving CFSME breachers and range staff and CAF controls, 35 post-concussive symp toms were also elevated among those with a history of concussion and warzone deployment. Th e authors examined those associations in this dataset.…”
Section: Analysis Began By Investigating Relevant Aspects Of Par Tici...mentioning
confidence: 76%
See 3 more Smart Citations
“…In earlier research involving CFSME breachers and range staff and CAF controls, 35 post-concussive symp toms were also elevated among those with a history of concussion and warzone deployment. Th e authors examined those associations in this dataset.…”
Section: Analysis Began By Investigating Relevant Aspects Of Par Tici...mentioning
confidence: 76%
“…[11][12][13][14][15] In contrast, data collected from samples of breachers from CANSOFCOM and CFSME showed that, whereas breachers and range staff report elevated levels of postconcussive symptoms, they did not report poorer men tal health outcomes, at least as measured by the RAND SF-36 or the PCL-5. 30,35 This study was conducted to replicate and extend those findings in two ways. First, beyond PTSD (PCL-5) and a measure of emotional well-being (RAND SF-36), measures of mental health were broadened to also include the Brief Symptom Inventory (BSI-18) -a self-report measure covering nine symptom dimensions that draw on three global indices of distress including anxiety, depression, and somatization.…”
Section: Present Study: Breachers and Snipersmentioning
confidence: 88%
See 2 more Smart Citations
“…Regardless of the mechanism, post-blast neurocognitive deficits have been demonstrated in animal models and humans ( 10 , 11 ). Repetitive low-level blasts, while unlikely to cause mechanical trauma via acceleration and/or rotation of the head, nevertheless result in neuropsychological and neurocognitive deficits and generally decreased physical and mental health ( 7 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%